On subgroups lifting modulo central commutant - Sergeychuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider a finitely generated group G with the commutant of odd order \(p_1^n_1 … p_s^n_s \) located at the center and prove that there exists a decomposition of G/G′ into the direct product of indecomposable cyclic groups such that each factor except at most n l + ... + n s factors lifts modulo commutant.